PENGUATAN MOTIVASI SHALAT DAN KARAKTER PESERTA DIDIK MELALUI PENDEKATAN PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Arsyad Arsyad; Wahyu Bagja Sulfemi; Tia Fajartriani (POTENSIA: Jurnal Kependidikan Islam, 2020)
The study was conducted at the Leuwiliang Sub-District Middle School in Bogor Regency with a population of all 7th grade students from 3 Public Middle Schools in Leuwiliang Subdistrict namely 1 Leuwiliang State Middle School, Leuwiliang 2 Junior High School with, and Leuwiliang 3 Public Middle School with total number of 396 students. The number of samples taken was taken 10%, namely 40 people using random sampling techniques. The method used is descriptive method that is making a systematic, factual and accurate descriptive of facts and the relationship between the phenomena investigated, with the aim of testing hypotheses that state whether or not there is a relationship between independent variables (X1) and (X2) with dependent variables (Y). Referring to the results of the regression test and correlation, then there is the influence of the contextual learning method on PAI towards strengthening prayer motivation. There is the influence of the contextual learning method on PAI towards strengthening the character of students. There is the influence of contextual learning methods on Islamic Education Educator on strengthening prayer motivation and strengthening the character of students. With a contextual approach to learning Islamic Education in schools providing knowledge, appreciation and encouraging students to practice and associate it in everyday life, because they feel the wisdom and benefits in real life.